Respuesta :

Answer:

The answer to your question is below

Step-by-step explanation:

11)   3x² - 3 = 267

      3x² = 267 + 3

      3x² = 270

      x² = 270 / 3

      x² = 90

     x = ± [tex]3\sqrt{10}[/tex]

12) 3r² + 6 = 33

     3r² = 33 - 6

     3r² = 27

       r² = 27/3

       r² = 9

       r = ± [tex]\sqrt{9}[/tex]

       r = ± 3

13)   9x² + 10 = 19

       9x² = 19 - 10

      9x² = 9

        x² = 9/9

        x² = 1

       x = ± 1

14) 9r² - 2 = -146

     9r² = -146 + 2

     9r² = -144

       r² = -144/9

       r = ± [tex]\sqrt{\frac{-144}{9}}[/tex]

       r = ± [tex]\frac{12i}{3}[/tex]

15) 2m² - 1 = 49

     2m² = 49 + 1

     2m² = 50

       m² = 50 / 2

       m² = 25

      m = ± 5

16) 4m² + 7 = 183

     4m² = 183 - 7

     4m² = 176

       m² = 176/4

       m² = 44

       m = ± [tex]\sqrt{44}[/tex]

       m = ±2[tex]\sqrt{11}[/tex]

17) 8p² + 3 = -93

    8p² = -93 - 3

    8p² = - 96

    p² = -96/8

    p² = -12

    p = ± [tex]\sqrt{-12}[/tex]

    p = ± [tex]2i\sqrt{3}[/tex]

18) 9p² + 5 = 446

    9p² = 446 - 5

    9p² = 441

      p² = 441/9

      p² = 49

      p = ± [tex]\sqrt{49}[/tex]

      p = ± 7

ACCESS MORE